Examining individual, health service, and experience of care determinants of patients’ satisfaction - A cross-sectional facility-based study in KP, Pakistan - Laurène Petitfour; Stephan Brenner; Khalid Rehman; Swati Srivastava; Asad Ullah; Zohaib Khan; Manuela De Allegri (PLoS ONE, 2026)
Health systems aim to meet populations’ needs and to spur their satisfaction, requiring to first understand what drives this satisfaction, and whether these drivers come from the health system or not. In this empirical study, we use survey data from 666 patients exiting outpatient services of 60 public and 62 private health facilities in four districts of the province of Khyber Pakhtunkhwa, Pakistan. The survey tool assessed patients’ socio-economic status, satisfaction with health service provision, and experiences of care (respect of privacy, out-of-pocket expenditures, availability of drugs). First, we synthesized the 16 items relating to satisfaction into a 12-item scale Patient Satisfaction score, relying on a Principal Component Analysis. Second, we used this score as the outcome in a linear model to identify its determinants. We found a generally high level of satisfaction regarding outpatient services within the sample, with an average satisfaction score of 76.37 out of 100. We did not find any association between satisfaction characteristics of the environment (type of facility, district). Women displayed significantly lower (−16%) and insured patients significantly higher (+6%) satisfaction scores. Indicators of healthcare experiences were found to be the strongest determinants of satisfaction, namely: satisfaction scores were 12% higher when privacy was respected, 5% higher when prescribed drugs were available and they also varied with the amount of healthcare expenses (positively and then negatively). Our results highlight the importance of designing policies that address the needs of specific population sub-groups and of ensuring access to core aspects of healthcare delivery, as reflected in patients’ experiences, across all facility types.